2019
DOI: 10.3390/fluids4020069
|View full text |Cite
|
Sign up to set email alerts
|

Turbulence and Microprocesses in Inhomogeneous Solar Wind Plasmas

Abstract: The random density fluctuations observed in the solar wind plasma crucially influence on the Langmuir wave turbulence generated by energetic electron beams ejected during solar bursts. Those are powerful phenomena consisting of a chain of successive processes leading ultimately to strong electromagnetic emissions. The small-scale processes governing the interactions between the waves, the beams and the inhomogeneous plasmas need to be studied to explain such macroscopic phenomena. Moreover, the complexity indu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 145 publications
(290 reference statements)
2
6
0
Order By: Relevance
“…When the plasma is randomly inhomogeneous (ΔN = 0.05), the behavior of the beam is very different, as, after a slightly stronger deceleration rate than for ΔN = 0, it starts to accelerate whereas W t jointly damps (Figure 1(a)), gaining during several thousands of plasma periods (ω p t  1000) roughly half the energy lost during wave growth (ω p t  1000), mostly due to electrostatic wave energy scattering in k-space and its further damping (see also the black solid line in Figure 1(d)). Such a phenomenon was also observed in previous works, when studying Langmuir wave turbulence generated by weak beams in 1D randomly inhomogeneous plasmas (Krafft et al 2013;Krafft & Volokitin 2016Krafft et al 2019).…”
Section: Waves' and Particles' Energiessupporting
confidence: 84%
“…When the plasma is randomly inhomogeneous (ΔN = 0.05), the behavior of the beam is very different, as, after a slightly stronger deceleration rate than for ΔN = 0, it starts to accelerate whereas W t jointly damps (Figure 1(a)), gaining during several thousands of plasma periods (ω p t  1000) roughly half the energy lost during wave growth (ω p t  1000), mostly due to electrostatic wave energy scattering in k-space and its further damping (see also the black solid line in Figure 1(d)). Such a phenomenon was also observed in previous works, when studying Langmuir wave turbulence generated by weak beams in 1D randomly inhomogeneous plasmas (Krafft et al 2013;Krafft & Volokitin 2016Krafft et al 2019).…”
Section: Waves' and Particles' Energiessupporting
confidence: 84%
“…Qualitatively, the Pearson type IV distribution has an asymmetric bell shape with heavy tails. It has been used for modeling various random processes, including wind shear fluctuations [21], fluctuating pressure on aircraft skin panels [22], and solar wind intensity [23]. The random noise in our simulations is generated using the procedures described by McGrath and Irving [24].…”
Section: Examples Of Applicationmentioning
confidence: 99%
“…All phenomena of reflection, refraction, and tunneling of waves are taken into account in the simulations. The initial levels of the Langmuir waves' and fluctuations' spectra are chosen according to realistic conditions; their profiles take into account possible anisotropies and the expected wavevector ranges, inferred from results obtained during one-dimensional studies performed by the authors (Volokitin et al 2013;Krafft et al 2013Krafft et al , 2015Krafft et al , 2019, 2016bVoshchepynets et al 2017). The rotational part of the calculated electronic current generates the induced electromagnetic wave fields as a result of the conversion, at constant frequency, of the electrostatic wave turbulence.…”
Section: Electromagnetic Wave Radiation By a Turbulent Plasma With Ramentioning
confidence: 99%
“…For example, satellites' measurements revealed that density fluctuations δn around several percent of the average background plasma density n 0 exist in the solar wind, with length scales around a few hundreds of kilometers (Mugundhan et al 2017;Chen et al 2018;Krupar et al 2018). These fluctuations, even when weak, affect the development of the electron beam instability and of the intensity and the spectra of the emerging Langmuir wave turbulence (Volokitin et al 2013;Krafft et al 2013Krafft et al , 2015Krafft et al , 2019, 2016bVoshchepynets et al 2017). In particular, it was shown (Krafft et al 2015;Krafft & Volokitin 2016a) that the electrostatic decay  ¢ +    is less efficient and more localized in space and time in a plasma with density fluctuations than in a uniform plasma.…”
Section: Introductionmentioning
confidence: 99%